Corporate Governance and Equity Prices - Gompers, P.; Ishii, J.; Metrick, A. (Quarterly Journal of Economics, 2003)
Shareholder rights vary across firms. Using the incidence of 24 governance rules, we construct a “Governance Index” to proxy for the level of shareholder rights at about 1500 large firms during the 1990s. An investment strategy that bought firms in the lowest decile of the index (strongest rights) and sold firms in the highest decile of the index (weakest rights) would have earned abnormal returns of 8.5 percent per year during the sample period. We find that firms with stronger shareholder rights had higher firm value, higher profits, higher sales growth, lower capital expenditures, and made fewer corporate acquisitions.